The Black-headed Duck Heteronetta atricapilla lays ordinary eggs - Mallory, Mark L (Wildfowl, 2000)
The Black-headed Duck Heteronetta atricapilla is the only known obligate parasite among the waterfowl. As such, it is predicted that the eggs of this species would exhibit some of the specialized characteristics observed in the eggs of obligately parasitic passerines. Contrary to expectations, the eggs of this duck were neither rounder nor with a thicker shell than expected for eggs of this size. It is speculated that the lack of destructive responses by host species to eggs of this duck in their nest may not have favoured evolution of stronger eggs in this parasite.